Haunted Sketches: Analyzing the Foundations of Horror in Early Works by Tove Jansson and Walt Disney - Płuciennik, Jarosław; Suvilehto, Pirjo (Zagadnienia Rodzajów Literackich, 2025)
This article explores the early artistic influences and beginnings of Tove Jansson and Walt Disney, focusing on their works’ gothic and surreal elements. Both Jansson and Disney are renowned for their contributions to children’s entertainment, yet their creations are complex and multifaceted, often transcending the boundaries of “children’s art.” While prominent, the idyllic nature of their works is intertwined with darker, more surreal themes. Jansson’s Moomin characters, initially depicted with fiery eyes and horn-like ears, reflect a blend of horror and Expressionism, influenced by her visits to Germany and many other European cities. Similarly, Disney’s early animations, such as Skeleton Dance, showcases a macabre and anarchic energy, pushing the boundaries of enchantment and the uncanny in mainstream avant-garde cartoons. The article delves into the surrealist techniques and aesthetic qualities in Jansson’s and Disney’s early works, highlighting their impact on popular culture and their ability to enchant and liberate through horror.